Literary Geography: Applying Geocriticism in "The Mermaid Madonna" by Stratis Myrivilis - Maria Margariti (European Journal of Geography)
This study uses the Geocritical method, as systematized by Bertrand Westphal in 2007, and applies it to the Greek novel The Mermaid Madonna by StratisMyrivilis for the first time. This novel uses as setting the settlement of Skala Skamnias or Mourias, which is located on Lesvos (an island of Greece in the North-Eastern Aegean Sea) after the Asia Minor Disaster in 1922 and after the arrival of the Greek refugees from Asia Minor to the island. The purpose of the study is to show how Geography is related to Literature and how the author deliberately chose Skala as the setting for his literary work in order to support his new perception of the concept of Greekness, as in his opinion it was formed after 1922.Thus, this article, first presents the Geocritical method and its use in the chosen novel and then applies it to the novel discussing how the author uses the place and time.